Antituberculosis agent diaportheone B: synthesis, absolute configuration assignment, and anti-TB activity of its analogues - Swaroop, Pandrangi Siva; Raut, Gajanan N.; Gonnade, Rajesh G.; Verma, Priyanka; Gokhale, Rajesh S.; Reddy, D. Srinivasa (Organic & Biomolecular Chemistry, 2012)
First synthesis of diaportheone B, an antituberculosis agent isolated from endophytic fungus Diaporthe sp. P133 is reported using two complementary routes, a one step and a three-step sequence. The absolute configuration of diaportheone B was determined by using X-ray crystal structure analysis of its dibromo derivative. In addition, we have prepared several close analogues of diaportheone B and determined their anti-TB potential using Alamar-blue assay (H(37)Rv).

Synthesis of isomeric corniculatolides - Raut, Gajanan N.; Chakraborty, Kasturi; Verma, Priyanka; Gokhale, Rajesh S.; Reddy, D. Srinivasa (Tetrahedron Letters, 2012)
Synthesis of three natural macrolides 11-O-methylcorniculatolide A, 11-O-methylisocorniculatolide A and isocorniculatolide A is reported using a simple, straight forward and high-yielding route. The present synthesis confirms the assigned molecular structures and provides an access to sufficient quantities of the natural products for the biological evaluation. In addition, we have determined the anti-TB potential of the three natural compounds using Alamar-Blue assay (H(37)Rv) and found no significant inhibitory activity at 100 mu g/ml. Excellent yields, short sequence and useful SAR information are the highlights of the present work. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Diaryl ether; Isocorniculatolide; Macrocyclization; Mitsunobu reaction; Total synthesis

IFN-gamma signaling maintains skin pigmentation homeostasis through regulation of melanosome maturation - Natarajan, Vivek T.; Ganju, Parul; Singh, Archana; Vijayan, Vinaya; Kirty, Kritika; Yadav, Shalini; Puntambekar, Shraddha; Bajaj, Sonali; Dani, Prachi P.; Kar, Hemanta K.; Gadgil, Chetan J.; Natarajan, Krishnamurthy; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2014)
Cellular homeostasis is an outcome of complex interacting processes with nonlinear feedbacks that can span distinct spatial and temporal dimensions. Skin tanning is one such dynamic response that maintains genome integrity of epidermal cells. Although pathways underlying hyperpigmentation cascade are recognized, negative feedback regulatory loops that can dampen the activated melanogenesis process are not completely understood. In this study, we delineate a regulatory role of IFN-gamma in skin pigmentation biology. We show that IFN-gamma signaling impedes maturation of the key organelle melanosome by concerted regulation of several pigmentation genes. Withdrawal of IFN-gamma signal spontaneously restores normal cellular programming. This effect in melanocytes is mediated by IFN regulatory factor-1 and is not dependent on the central regulator microphthalmia-associated transcription factor. Chronic IFN-gamma signaling shows a clear hypopigmentation phenotype in both mouse and human skin. Interestingly, IFN-gamma KO mice display a delayed recovery response to restore basal state of epidermal pigmentation after UV-induced tanning. Together, our studies delineate a new spatiotemporal role of the IFN-gamma signaling network in skin pigmentation homeostasis, which could have implications in various cutaneous depigmentary and malignant disorders.
Keywords: detanning; gene regulation; interferon; melanin

Permeation of lipidated protein in bilayer using unbiased simulations reveals signature motif for protein-membrane binding - Thukral, Lipi; Sengupta, Durba; Gokhale, Rajesh S. (Biophysical Journal, 2014)

Molecular mechanism underlying recruitment and insertion of lipid-anchored LC3 protein into membranes - Thukral, Lipi; Sengupta, Durba; Ramkumar, Amrita; Murthy, Divya; Agrawal, Nikhil; Gokhale, Rajesh S. (Biophysical Journal, 2015)
Lipid modification of cytoplasmic proteins initiates membrane engagement that triggers diverse cellular processes. Despite the abundance of lipidated proteins in the human proteome, the key determinants underlying membrane recognition and insertion are poorly understood. Here, we define the course of spontaneous membrane insertion of LC3 protein modified with phosphatidylethanolamine using multiple coarse-grain simulations. The partitioning of the lipid anchor chains proceeds through a concerted process, with its two acyl chains inserting one after the other. Concurrently, a conformational rearrangement involving the alpha-helix III of LC3, especially in the three basic residues Lys(65), Arg(68), and Arg(69), ensures stable insertion of the phosphatidylethanolamine anchor into membranes. Mutational studies validate the crucial role of these residues, and further live-cell imaging analysis shows a substantial reduction in the formation of autophagic vesicles for the mutant proteins. Our study captures the process of water-favored LC3 protein recruitment to the membrane and thus opens, to our knowledge, new avenues to explore the cellular dynamics underlying vesicular trafficking.

Repurposing of a drug scaffold: identification of novel sila analogues of rimonabant as potent antitubercular agents - Ramesh, Remya; Shingare, Rahul D.; Kumar, Vinod; Anand, Amitesh; Swetha, B.; Veeraraghavan, Sridhar; Viswanadha, Srikant; Ummanni, Ramesh; Gokhale, Rajesh S.; Reddy, D. Srinivasa (European Journal of Medicinal Chemistry, 2016)
The structural similarity between an MmpL3 inhibitor BM212, and a cannabinoid receptor modulator rimonabant, prompted us to investigate the anti-tubercular activity of rimonabant and its analogues. Further optimization, particularly through incorporation of silicon into the scaffold, resulted in new compounds with significant improvement in anti-tubercular activity against Mycobacterium tuberculosis (H37Rv). The sila analogue 18a was found to be the most potent antimycobacterial compound (MIC, 31 ng/mL) from this series with an excellent selectivity index. (C) 2016 Elsevier Masson SAS. All rights reserved.

Mapping architectural and transcriptional alterations in non-lesional and lesional epidermis in vitiligo - Singh, Archana; Gotherwal, Vishvabandhu; Junni, Paivi; Vijayan, Vinaya; Tiwari, Manisha; Ganju, Parul; Kumar, Avinash; Sharma, Pankaj; Fatima, Tanveer; Gupta, Aayush; Holla, Ananthaprasad; Kar, Hemanta K.; et al. (Scientific Reports, 2017)
In vitiligo, chronic loss of melanocytes and consequent absence of melanin from the epidermis presents a challenge for long-term tissue maintenance. The stable vitiligo patches are known to attain an irreversible depigmented state. However, the molecular and cellular processes resulting in this remodeled tissue homeostasis is unclear. To investigate the complex interplay of inductive signals and cell intrinsic factors that support the new acquired state, we compared the matched lesional and non-lesional epidermis obtained from stable non-segmental vitiligo subjects. Hierarchical clustering of genome-wide expression of transcripts surprisingly segregated lesional and non-lesional samples in two distinct clades, despite the apparent heterogeneity in the lesions of different vitiligo subjects. Pathway enrichment showed the expected downregulation of melanogenic pathway and a significant downregulation of cornification and keratinocyte differentiation processes. These perturbations could indeed be recapitulated in the lesional epidermal tissue, including blunting of rete-ridges, thickening of stratum corneum and increase in the size of corneocytes. In addition, we identify marked increase in the putrescine levels due to the elevated expression of spermine/spermidine acetyl transferase. Our study provides insights into the intrinsic self-renewing ability of damaged lesional tissue to restore epidermal functionality in vitiligo.

Kupyaphores are zinc homeostatic metallophores required for colonization of Mycobacterium tuberculosis - Mehdiratta, Kritee; Singh, Shubham; Sharma, Sachin; Bhosale, Rashmi S.; Choudhury, Rahul; Masal, Dattatraya P.; Manocha, Alzu; Dhamale, Bhushan Dilip; Khan, Naseem; Asokachandran, Vivekanand; Sharma, Pooja; Ikeh, Melanie; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2022)
Mycobacterium tuberculosis (Mtb) endures a combination of metal scarcity and toxicity throughout the human infection cycle, contributing to complex clinical manifestations. Pathogens counteract this paradoxical dysmetallostasis by producing specialized metal trafficking systems. Capture of extracellular metal by siderophores is a widely accepted mode of iron acquisition, and Mtb iron-chelating siderophores, mycobactin, have been known since 1965. Currently, it is not known whether Mtb produces zinc scavenging molecules. Here, we characterize low-molecular-weight zinc-binding compounds secreted and imported by Mtb for zinc acquisition. These molecules, termed kupyaphores, are produced by a 10.8 kbp biosynthetic cluster and consists of a dipeptide core of ornithine and phenylalaninol, where amino groups are acylated with isonitrilecontaining fatty acyl chains. Kupyaphores are stringently regulated and support Mtb survival under both nutritional deprivation and intoxication conditions. A kupyaphore-deficient Mtb strain is unable to mobilize sufficient zinc and shows reduced fitness upon infection. We observed early induction of kupyaphores in Mtb-infected mice lungs after infection, and these metabolites disappeared after 2 wk. Furthermore, we identify an Mtb-encoded isonitrile hydratase, which can possibly mediate intracellular zinc release through covalent modification of the isonitrile group of kupyaphores. Mtb clinical strains also produce kupyaphores during early passages. Our study thus uncovers a previously unknown zinc acquisition strategy of Mtb that could modulate host-pathogen interactions and disease outcome.
Keywords: metallophore; nutritional immunity; tuberculosis; zinc

Temporal analysis of melanogenesis identifies fatty acid metabolism as key skin pigment regulator - Sultan, Farina; Basu, Reelina; Murthy, Divya; Kochar, Manisha; Attri, Kuldeep S.; Aggarwal, Ayush; Kumari, Pooja; Dnyane, Pooja; Tanwar, Jyoti; Motiani, Rajender K.; Singh, Archana; Gadgil, Chetan; et al. (Plos Biology, 2022)
Therapeutic methods to modulate skin pigmentation has important implications for skin cancer prevention and for treating cutaneous hyperpigmentary conditions. Towards defining new potential targets, we followed temporal dynamics of melanogenesis using a cell-autonomous pigmentation model. Our study elucidates 3 dominant phases of synchronized metabolic and transcriptional reprogramming. The melanogenic trigger is associated with high MITF levels along with rapid uptake of glucose. The transition to pigmented state is accompanied by increased glucose channelisation to anabolic pathways that support melanosome biogenesis. SREBF1-mediated up-regulation of fatty acid synthesis results in a transient accumulation of lipid droplets and enhancement of fatty acids oxidation through mitochondrial respiration. While this heightened bioenergetic activity is important to sustain melanogenesis, it impairs mitochondria lately, shifting the metabolism towards glycolysis. This recovery phase is accompanied by activation of the NRF2 detoxication pathway. Finally, we show that inhibitors of lipid metabolism can resolve hyperpigmentary conditions in a guinea pig UV-tanning model. Our study reveals rewiring of the metabolic circuit during melanogenesis, and fatty acid metabolism as a potential therapeutic target in a variety of cutaneous diseases manifesting hyperpigmentary phenotype.

Synthesis, biological evaluation and docking studies of silicon incorporated diarylpyrroles as MmpL3 inhibitors: an effective strategy towards development of potent anti-tubercular agents - Vasudevan, N.; Motiwala, Zenia; Ramesh, Remya; Wagh, Sachin B.; Shingare, Rahul D.; Katte, Revansiddha; Anand, Amitesh; Choudhary, Sushil; Kumar, Ajay; Gokhale, Rajesh S.; Kulkarni, Kiran A.; Reddy, D. Srinivasa (European Journal of Medicinal Chemistry, 2023)
Growing global demand for new molecules to treat tuberculosis has created an urgent need to develop novel strategies to combat the menace. BM212 related compounds were found to be potent anti-TB agents and they inhibit mycolic acid transporter, MmpL3, a known potent drug target from Mycobacterium tuberculosis. In order to enhance their inhibitory potency, several silicon analogues of diarylpyrroles related to BM212 were designed, synthesized, and evaluated for anti-tubercular activities. In Alamar blue assay, most of the silicon-incorporated compounds were found to be more potent than the parent compound (BM212), against Mycobacterium tuberculosis (MIC = 1.7 & mu;M, H37Rv). Docking results from the crystal structure of MmpL3 and silicon analogues as pharmacophore model also strongly correlate with the biological assays and suggest that the incorporation of silicon in the inhibitor scaffold could enhance their potency by stabilizing the hydrophobic residues at the binding pocket. The best docking hit, compound 12 showed an MIC of 0.1 & mu;M against H37Rv with an acceptable in vitro ADME profile and excellent selectivity index. Overall, the present study indicates that, the designed silicon analogues, especially compound 12 could be a good inhibitor for an intrinsically flexible drug-binding pocket of MmpL3 and has potential for further development as anti-tubercular agents.
Keywords: antibiotic; BM212; docking studies; MmpL3 inhibitor; Silicon analogue; tuberculosis

Enzymatic pathway for kupyaphore degradation in mycobacterium tuberculosis: mechanism of metal homeostasis and turnover - Bhosale, Rashmi S.; Chakraborty, Arnab; Wong, Tsung-Yun; Masal, Dattatraya P.; Choudhury, Rahul; Srivastava, Sonali; Reddy, D. Srinivasa; Aldrich, Courtney C.; Kamat, Siddhesh S.; Mohanty, Debasisa; Gokhale, Rajesh S. (ACS Chemical Biology, 2025)
Metallophores are essential for metal homeostasis, regulating availability, and mediating host-pathogen interactions. Kupyaphores are specialized metallophores produced by Mycobacterium tuberculosis (Mtb) that primarily chelate zinc to support bacterial survival. Elevated kupyaphore levels early in infection highlight their importance, while their rapid decline, despite increasing bacterial loads, indicates tightly regulated mechanisms of production, consumption, and degradation. However, the processes driving kupyaphore catabolism and their role in preventing zinc toxicity in Mtb remain unclear. Here, we show that covalent modification of the isonitrile moiety in kupyaphores releases zinc, triggering degradation through a sequential three-step enzymatic pathway encoded by Mtb. Isonitrile hydratase converts isonitrile groups into formamides, which are subsequently processed into amines by N-substituted formamide deformylase and ultimately oxidized to beta-ketoesters by amine oxidases. The biological significance of this pathway is underscored by the upregulation of these genes under metal-depleted and biofilm-forming conditions. Mutant Mtb strains lacking these genes exhibit impaired growth in metal-limiting environments and reduced levels of biofilm formation. Catalytic intermediates detected in Mtb cultures and infected mouse lung tissues confirm the pathway's in vivo activity. Further, genome mining reveals that similar enzymes are conserved across organisms producing isonitrile-containing metabolites, emphasizing the broader importance of this pathway. Understanding these processes could pave the way for novel therapeutic strategies targeting kupyaphore catabolism.

Novel routes for bioproduction of delta lactone aroma compounds - Srivastava, Sonali; Chandramouli, Aakash; Gupta, Payal; Manzer, Abdur Rahman; Choudhury, Rahul; Reddy, D. Srinivasa; Yazdani, Syed Shams; Kamat, Siddhesh S.; Mohanty, Debasisa; Nandicoori, Vinay K.; Gokhale, Rajesh S. (Metabolic Engineering, 2026)
Delta lactones are fatty acid-derived aroma compounds that hold tremendous commercial value. As consumer demand for natural flavours continues to rise, the bioproduction of S-lactones, including S-decalactone and S-dodecalactone, is attracting substantial interest. Our study brings forth a novel approach to the bioproduction of S-lactones from glucose, deviating from existing methods that primarily rely on the biotransformation of fatty acids. The high cost of fatty acid raw material constrains the commercial viability of this traditional approach. We engineered surface-lipid producing type I polyketide synthase (PKS) from Mycobacterium smegmatis by incorporating macrolactone thioesterase (TE) domain. Two out of three fusion constructs produced an appropriately engineered PKS-TE fusion protein that facilitated the synthesis of S-lactones. When grown on glucose as the sole carbon source, recombinant E. coli expressing the engineered PKS-TE fusion protein successfully made S-lactones ranging from C8-C18 acyl chains. Our research further highlights the potential of Mycobacterium smegmatis as a cell factory for producing fatty acid-based S-lactones. By genetically designing and engineering Mycobacterium smegmatis to express PKS-TE fusion protein, we achieved bioproduction of various S-lactones. Batch fermentation of the engineered E. coli strain fed with 2 % glucose produced 786 mg/L of S-dodecalactone and 444 mg/L of S-decalactone at 120 h, underscoring the efficacy of our approach. Thus, this study is the first to demonstrate a methodology for redirecting primary metabolic intermediates towards S-lactone biosynthesis in engineered bacteria, enabling the use of inexpensive and renewable feedstocks.
Keywords: Natural flavour; PKS engineering; S-decalactone; S-dodecalactone; S-lactone